Minocycline can reduce testicular apoptosis related to varicocele in male rats. (9th March 2022) - Shokoohi, Majid; Khaki, Arash; Roudi Rasht Abadi, Ayda; MohammadZadeh Boukani, Linda; Hassanpour Khodaie, Sepideh; Kalarestaghi, Hossein; Khaki, Amir Afshin; Moghimian, Maryam; Niazkar, Hamid Reza; Shoorei, Hamed
Abstract: The current research aimed to assess the impacts of Minocycline on varicocele‐induced regulation of apoptotic‐related genes and oxidative stress in the testis of adult Wistar rats. Thirty‐two rats were divided into 4 groups: sham, varicocele (VcI), varicocele treated with Minocycline (VcI + Mno) for 56 days and healthy rats treated with minocycline (Mno). After 8 weeks, the oxidative stress markers levels in serum were investigated, afterwards, the level of Bax and Bcl‐2 expression were assessed through 'immunocytochemistry' and RT‐qPCR assays. Also, the rate of apoptosis was evaluated through the TUNEL method. Johnson's score, 'the width of epithelium' and 'seminiferous tubules diameter' were ameliorated in the VcI + Mno group in comparison with the Vcl group. Administration of Minocycline raised the 'Glutathione peroxidase' and 'Superoxide dismutase' levels in serum and declined the Malondialdehyde level in serum ( p  = 0.001). Furthermore, current study represented that minocycline reduced Bax and enhanced the expression of Bcl‐2 gene and protein in comparison with the Vcl group ( p  < 0.05). In addition, Minocycline administration significantly declined the rate of apoptosis in germ cells ( p  < 0.05). Our study demonstrated that the administration of Minocycline could improve testicular injury in varicocele‐induced rats by its antioxidant activity.